Gambaran Pengelolaan Gangguan Persepsi Sensori: Halusinasi Pendengaran dan Penglihatan pada Klien Skizofrenia Paranoid: Description of Management of Sensory Perception Disorders: Auditory and Visual Hallucinations in Paranoid Schizophrenic Clients - Ela Safitri; Ana Puji Astuti (Journal of Holistics and Health Sciences (JHHS), 2023)
Hallucinations are one of the symptoms of mental disorders in which the client experiences changes in sensory perception, feels false assumptions in the form of sound, sight, taste, touch or smell. The client feels a stimulus that is not real. The purpose of writing this scientific paper is to describe the management of sensory perception disorders: auditory and visual hallucinations with paranoid schizophrenia at Wisma Setyowati Mental Hospital Prof. Dr. Soerojo Magelang. The approach method in compiling this Scientific Paper is a descriptive method because it is used for nursing care outcomes that focus on one of the main priority problems. The data collection technique uses a nursing methodological approach starting from assessment, nursing diagnosis, nursing intervention and evaluation. The implementation of nursing is carried out for 3 days by controlling the client's hallucinations, among others: by rebuking, taking medication properly, conversing with other people and doing positive activities. The results of the nursing evaluation, hearing and vision sensory perception disorders were partially resolved. Suggestions for the community and families can change the mindset / thoughts and views of clients with mental disorders with hallucinations and can accept them without being isolated in their environment. Increase knowledge about mental disorders in order to be able to overcome and treat clients who experience hallucinations, and so that clients can mingle and be open about the problems they are experiencing.   ABSTRAK Halusinasi merupakan salah satu gejala gangguan jiwa yang mana klien mengalami perubahan sensori persepsi, merasa berpraduga palsu berupa suara, penglihatan, pengecapan, perabaan atau penghiduan. Klien merasakan stimulus yang sebenarnya tidak nyata. Tujuan penulisan karya ilmiah ini adalah untuk mendeskripsikan tentang pengelolaan gangguan persepsi sensori: halusinasi pendengaran dan penglihatan dengan skizofrenia paranoid di Wisma Setyowati Rumah Sakit Jiwa Prof. Dr. Soerojo Magelang. Metode pendekatan dalam menyusun Karya Tulis Ilmiah ini adalah metode deskriptif karena digunakan untuk hasil asuhan keperawatan yang menitikberatkan pada salah satu masalah prioritas utama. Teknik pengumpulan data menggunakan pendekatan proses asuhan keperawatan meliputi pengkajian, diagnosis keperawatan, intervensi keperawatan dan evaluasi. Implementasi keperawatan dilakukan selama 3 hari dengan melakukan mengontrol halusinasi klien antara lain yaitu: dengan cara menghardik, 5 benar minum obat, bercakap-cakap dengan orang lain dan melakukan kegiatan yang positif. Hasil evaluasi keperawatan, gangguan persepsi sensori pendengaran dan penglihatan teratasi sebagian. Saran bagi masyarakat dan keluarga dapat merubah mindset/pikiran serta pandangannya terhadap klien dengan gangguan jiwa dengan halusinasi dan dapat menerimanya tanpa mengucilkan di lingkungannya. Menambah pengetahuan mengenai gangguan jiwa agar dapat mengatasi dan merawat klien yang mengalami halusinasi, serta agar klien dapat berbaur dan terbuka mengenai masalah yang dialaminya.